ANALISIS DAN PERANCANGAN SISTEM PELAYANAN PASIEN RAWAT JALAN DI KLINIK PRATAMA PANTI WALUYO SURAKARTA - Sri Huning Anwariningsih; Astri Charolina; Martha Kristiana (JURNAL GAUNG INFORMATIKA, 2015)
Outpatient information system is a system that provides information in the form of data in matters relating to outpatient. Outpatient services for patients are observation,diagnosis, treatment, medical rehabilitation and other health care services without a stay at the hospital. This resulted in a research of design and analysis system outpatient clinic Pratama Panti Waluyo Surakarta-based web. The research methodology used is the interview, observation, literature. Development is a process that is in all of these systems are displayed in one tab, input management of medical record and sales of automatic logging of drug registration of patients, the addition of the financial reports for the needs of the Central Administration and report medical record based on the name of the doctor that can be accessed by Admins and the officer of the clinic, as well as the look of the website were made more attractive.